DETERMINANTS OF FAST FOOD CONSUMPTION BEHAVIOR IN ADOLESCENTS IN THE CITY OF JAKARTA - Delvi Fitrianti; Retno Mardhiati; Cornelis Novianus (Jurnal Riset Kesehatan, 2023)
Fast food is high in calories and fat. Consuming fast food excessively can cause various health problems, including obesity. This study aims to determine the factors related to the behavior of fast food consumption in adolescents at SMA Negeri 30 Jakarta in 2022. The research design was quantitative with a cross-sectional approach. Data collection in this study was carried out in April - May 2022 with a population of 884. A total of 200 respondents as samples were collected and processed using the Quota Sampling sampling technique. This research employs univariate,  bivariate, and Chi-Square test analysis methods. The results of the univariate analysis of most categories showed that adolescents often consumed fast food (51%), female gender (59.5%), had good knowledge (65%), had a positive attitude (59%), had a positive body image (56%), has high pocket money (66.5%), is not affected by social media (68.5%), not affected by peers (78%) and unaffected by promotion (65%). The bivariate analysis showed a relationship between knowledge (p-value= 0.000; PR= 2.566; 95% CI= 1.661-3.963), body image (p-value= 0.035; PR= 1.381; 95% CI= 1.042-1.830) , pocket money (p-value= 0.046; PR= 1.369; 95% CI= 1.039-1.804), and the influence of promotion (p-value = 0.009; PR= 1.572; 95% CI= 1.109-2.229) on fast food consumption behavior.